Prescribing Anabolic Steroids for Cosmetic Muscle Enhancement justification: A Cross-Sectional Study Among Healthcare Trainees and Professionals - Thakur, Mohini; Nain, Abhishek; Choudhary, Shambhavi; Kaur, Avneet; Chaudhary, Eshita; Seth, Harsh Pratap; Garg, Hemant Kumar; Singh, Rukmini (Journal of Neonatal Surgery, 2025)
Background: The non-therapeutic use of anabolic steroids for cosmetic muscle enhancement raises ethical, medical, and regulatory concerns. This study explores the opinions of future and current healthcare professionals on whether physicians should be permitted to prescribe anabolic steroids for aesthetic purposes. Methods: A structured Likert-scale questionnaire was administered to 250 participants: 100 MBBS students, 50 nursing students, and 100 paramedical staff (including nurses and technicians). The survey assessed attitudes toward ethical permissibility, medical risks, societal impact, and regulatory control. Results: While 68% of MBBS students opposed cosmetic steroid prescriptions, only 42% of paramedical staff shared this view. Nursing students were split, with 50% neutral. Key concerns included long-term health risks (82%), potential for misuse (76%), and erosion of medical ethics (64%). Conclusion: The majority of respondents expressed reservations about prescribing anabolic steroids for cosmetic enhancement. The findings suggest a need for clearer ethical guidelines and educational interventions in medical curricula